Isolamento e propagação da cepa autóctone de Lawsonia intracellularis in vitro: e sua utilização em diagnóstico sorológico - Juliana Saes Vilaca de Oliveira (2012)
Extraction and isolation attempts of a South American strain of the bacterium Lawsonia intracellularis were made from swine intestine samples with gross lesions suggestive of proliferative enteropathy. Isolation was successfully performed from a sample with lesions that were compatible with porcine proliferative haemorrhagic enteropathy (PHE). The strain was propagated in vitro and characterized as a different genotypic pattern than other isolates (15-09- 15-09), by the variable number of tandem repeats (VNTR) technique. This new strain was used in the confection of 96 well plates for immunoperoxidase monolayer assay (IPMA) serological tests. Sera collected from 80 animals previously inoculated with L. intracellularis were used in ELISA and IPMA serological tests, and their sensitivities were calculated based on the results. The ELISA test had a sensitivity of 72.5%, which was lower than the IPMA, with a 95% sensitivity. There was no statistical association between the two serological tests. In conclusion, the first Latin American strain of L. intracellularis was successfully isolated and propagated in vitro, which made possible the execution of the IPMA serological test, with a higher sensitivity than the commercial ELISA.